Analysis of Factors Affecting the Delay of Submission of Health BPJS Claims in Kertosono General Hospital - Yuly Peristiowati; Wahyu Herwati Cahyo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Hospital claims are made collectively and billed to BPJS every month, accompanied by supporting documents, namely a photocopy of the BPJS card, referral letter, patient eligibility letter (SEP), nurse evidence, statement letter, fees to be paid. The purpose of this study is to analyze the effect of man, machine and method on delays in submitting BPJS Health claims at Kertosono Hospital. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe effect of man, machine and method on the delay in submitting BPJS Health claims at Kertosono Hospital. The total population of 164 respondents and a sample of 116 respondents were taken by using Simple Random Sampling technique. In the study, it was found that most of the respondents had sufficient category as many as 58 respondents (50%). Almost half of the respondents have enough machine category as many as 59 respondents (41%). Most of the respondents have the method in the sufficient category as many as 52 respondents (45%). Most of the respondents had delays in the moderately fluent category as many as 56 respondents (48%). Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that there is a simultaneous influence of man, machine & method for the delay in submitting BPJS Health claims at Kertosono Hospital with an effect of 81.2%. It is hoped that the hospital management can provide a good breakthrough to help the process of completing the files that will be submitted for BPJS claims with electronic medical records or with other things so that there will be no more delays in the future.